Pengembangan LKPD Berbasis Model Discovery Learning dengan Integrasi Etnosains pada Materi Kimia Asam Basa - Putri Malona Girsang; Eddiyanto Eddiyanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Chemistry learning on acid-base material still tends to be abstract and less related to everyday life, so innovative and contextual teaching materials are needed. This study aims to develop and determine the level of validity and response of teachers and students to LKPD based on discovery learning model with ethnoscience integration in acid-base chemistry material. This study is a research and development research (R&D) with a 4D model that was carried out up to the development stage involving expert validators, chemistry teachers, grade XI students as research subjects, using instruments in the form of validation sheets and Likert scale response questionnaires. The novelty of this study lies in the integration of the discovery learning model with an ethnoscience approach that links the concept of acid-base with local cultural phenomena, so that learning becomes contextual and meaningful. The results showed that the developed LKPD had a validity level of material experts of 80.42% (feasible category) and media experts of 81.87% (very feasible category). Teacher responses to LKPD were 96.79% and students' responses were 81.11% with a very feasible category. These results indicate that the developed worksheets are not only valid and practical, but also have the potential to enhance conceptual understanding and student engagement in learning, thus supporting more contextual and meaningful acid-base chemistry learning through connections to everyday life.